2019
DOI: 10.2217/fmb-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Genetically Diverse NDM-1, -5, -7 Producing-Gram-Negative Pathogens Isolated from Pediatric Patients in Pakistan

Abstract: Aim: To determine the prevalence of New Delhi metallo-β-lactamase (NDM)-producing Gram-negative pathogens isolated from children’s samples. Materials & methods: Carbapenem-resistant clinical isolates (n = 117) were confirmed by VITEK® 2 compact system, matrix-assisted laser desorption ionization–time of flight and multilocus sequence typing. MIC (μg/ml) of various antibiotics was determined by VITEK 2 compact system. Molecular characterization of the isolates was performed by PCR, DNA sequencing, PFGE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
3
31
2
Order By: Relevance
“…The association between ST101 and NDM-1 producers was recently described in Tunisia, 49 Italy, 50 and Pakistan. 51 In conclusion, this study reports for the first time the presence of CPKP in food-producing animals and specifically in chicken meat in Western Algeria. Our study supports implementation of a risk assessment for zoonotic CPE in the context of an endemic situation notably with the emergence of these bacteria in food-producing animals to prevent their occurrence and spread to humans and the environment.…”
Section: Discussionmentioning
confidence: 64%
“…The association between ST101 and NDM-1 producers was recently described in Tunisia, 49 Italy, 50 and Pakistan. 51 In conclusion, this study reports for the first time the presence of CPKP in food-producing animals and specifically in chicken meat in Western Algeria. Our study supports implementation of a risk assessment for zoonotic CPE in the context of an endemic situation notably with the emergence of these bacteria in food-producing animals to prevent their occurrence and spread to humans and the environment.…”
Section: Discussionmentioning
confidence: 64%
“…Conversely, NDM-1-producing CRKP was resistant to them, which were agreed with another report. 32 Interestingly, a study showed that NDM-5-producing KP strains have high resistance to quinolones, 35 while, other studies proposed controversial points. 10,13 Hence, the diversity of carbapenemases among CRKP strengthens the difficulty for infection control.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, A. baumannii was declared as the most resistant pathogen identified in this study. A. baumannii also ranked the second most commonly detected pathogen (24.7%) among a collection of carbapenemase producers obtained from one hospital in Lahore between 2015 and 2016 [6]. Furthermore, A. baumannii was the main isolated bacterium (39.8%) among a total of 113 isolates recovered from 80 ventilator-supported patients at the Foundation Hospital, Rawalpindi, in 2016 [7].…”
Section: Open Accessmentioning
confidence: 99%